Renewable Energy and Kaliandra Plant Utilization for Eco Edu Tourism - Nasython, Kun (Jurnal Indonesia Sosial Sains, 2025)
This research investigates the multifaceted potential of Kaliandra plant cultivation beyond its established use as a renewable energy source for wood pellets. The study highlights Kaliandra's significant capacity to enhance local economic income through eco-tourism, emphasizing the strategic role of direct and indirect benefits in empowering local communities by involving them as eco-tourism actors. Furthermore, the research underscores Kaliandra's crucial contribution to reducing carbon emissions. By integrating Kaliandra cultivation with eco-tourism and educational initiatives, the study concludes that the "Eco Edu Wisata Kaliandra" business model holds substantial promise and warrants further development. Future research should focus on optimizing this integrated bioenergy and eco-tourism model through economic viability studies and synergistic management practices, delve deeper into community empowerment and socio-economic impacts, quantify additional environmental benefits, and explore the scalability and policy implications for broader adoption.